Invasion of Lantana into India: analyzing introduction, spread, human adaptations and management - Hari Krishnan, Ramesh Kannan (Rhodes University, Faculty of Science, Department of Environmental Science, 2013)
Objectives and Research Questions 1. To reconstruct the history of invasion of Lantana in India from where, by who, and when was Lantana species introduced into India?, given its long history in the country, is it still spreading or has it become more or less stable? 2. To study the human adaptation to Lantana invasion: socioeconomic causes and consequences of the use of Lantana as an alternative source of livelihood for forest dependent communities in southern India; how have local communities adapted to the invasion?; what are the key determinants that may have driven communities to use Lantana?; what are the economic consequences of the use of Lantana by local communities? 3. To critically review local practices and forest policy for the management of Lantana in southern India.; how has the use of Lantana by local communities impacted its local regeneration?; does the use of Lantana in local context have implications for its management?; what has been the role of the Forest Department and its policies in managing Lantana?
Keywords: Lantana -- India; Weeds -- Control -- India; Plant introduction -- India; Natural resources -- India; Botany, Economic -- India; Botany -- Social aspects -- India